Pengaruh Teknik Distraksi Menggunakan Video Kartun Terhadap Nyeri Anak Saat Tindakan Invasif - A. Miftahul Khair (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Invasive procedures in children, such as IV insertion and blood sampling, often cause pain and anxiety that can lead to psychological trauma. One non-pharmacological intervention that can be used to reduce pain is distraction techniques using cartoon videos. This study aims to determine the effect of distraction techniques using cartoon videos on children's pain levels during invasive procedures. This study used a quantitative design with a quasi-experimental method using a pretest–posttest with control group approach. The study sample consisted of 60 children aged 3–10 years who were divided into an intervention group and a control group. Pain levels were measured using the Wong-Baker Faces Pain Rating Scale. Data analysis was performed using a paired t-test and independent t-test. The results showed a significant decrease in pain levels in the group given cartoon video distraction with a p-value < 0.05. It was concluded that the distraction technique using cartoon videos was effective in reducing pain in children during invasive procedures.